A General Safety Assessment for Purified Food Ingredients Derived From Biotechnology Crops: Case Study of Brazilian Sugar and Beverages Produced From Insect-Protected Sugarcane - Kennedy, Reese D.; Cheavegatti-Gianotto, Adriana; de Oliveira, Wladecir S.; Lirette, Ronald P.; Hjelle, Jerry J. (Frontiers in Bioengineering and Biotechnology, 2018)
Insect-protected sugarcane that expresses Cry1Ab has been developed in Brazil. Analysis of trade information has shown that effectively all the sugarcane-derived Brazilian exports are raw or refined sugar and ethanol. The fact that raw and refined sugar are highly purified food ingredients, with no detectable transgenic protein, provides an interesting case study of a generalized safety assessment approach. In this study, both the theoretical protein intakes and safety assessments of Cry1Ab, Cry1Ac, NPTII, and Bar proteins used in insect-protected biotechnology crops were examined. The potential consumption of these proteins was examined using local market research data of average added sugar intakes in eight diverse and representative Brazilian raw and refined sugar export markets (Brazil, Canada, China, Indonesia, India, Japan, Russia, and the USA). The average sugar intakes, which ranged from 5.1 g of added sugar/person/day (India) to 126 g sugar/p/day (USA) were used to calculated possible human exposure. The theoretical protein intake estimates were carried out in the “Worst-case” scenario, assumed that 1 μg of newly-expressed protein is detected/g of raw or refined sugar; and the “Reasonable-case” scenario assumed 1ng protein/g sugar. The “Worst-case” scenario was based on results of detailed studies of sugarcane processing in Brazil that showed that refined sugar contains less than 1 ug of total plant protein /g refined sugar. The “Reasonable-case” scenario was based on assumption that the expression levels in stalk of newly-expressed proteins were less than 0.1% of total stalk protein. Using these calculated protein intake values from the consumption of sugar, along with the accepted NOAEL levels of the four representative proteins we concluded that safety margins for the “Worst-case” scenario ranged from 6.9 × 105 to 5.9 × 107 and for the “Reasonable-case” scenario ranged from 6.9 × 108 to 5.9 × 1010. These safety margins are very high due to the extremely low possible exposures and the high NOAELs for these non-toxic proteins. This generalized approach to the safety assessment of highly purified food ingredients like sugar illustrates that sugar processed from Brazilian GM varieties are safe for consumption in representative markets globally.